2019
DOI: 10.1371/journal.pone.0225628
|View full text |Cite
|
Sign up to set email alerts
|

Questionable utility of digoxin in left-ventricular assist device recipients: A multicenter, retrospective analysis

Abstract: BackgroundWhile clinical experience with left ventricular assist devices (LVAD) continues to grow and evolve, little is known regarding the ongoing use of certain medications in this population. We sought to evaluate the utility of digoxin in LVAD recipients and its association with outcomes.MethodsA total of 505 patients who underwent continuous-flow LVAD implantation at 5 centers from 2007–2015 were included. Patients were divided into 4 groups: not on digoxin at any time (ND; n = 257), received digoxin pre … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 22 publications
1
1
0
Order By: Relevance
“…Balachandran et al showed that early digoxin use patients showed improved survival on univariate analysis that went away after multivariate analysis while Pinsino et al showed that digoxin use was associated with lower survival free from hemocompatibility-related adverse events. 22,23 Our results are similar to those published by Ahmed et al 24 in a multicenter, retrospective analysis that showed that digoxin use did not have any impact on post-LVAD survival.…”
Section: Discussionsupporting
confidence: 90%
“…Balachandran et al showed that early digoxin use patients showed improved survival on univariate analysis that went away after multivariate analysis while Pinsino et al showed that digoxin use was associated with lower survival free from hemocompatibility-related adverse events. 22,23 Our results are similar to those published by Ahmed et al 24 in a multicenter, retrospective analysis that showed that digoxin use did not have any impact on post-LVAD survival.…”
Section: Discussionsupporting
confidence: 90%
“…Digoxin prevents AVM-associated GI bleeding by inhibiting HIF-1a expression [28]. Although continuous digoxin use post-LVAD implantation reduces GI bleeding, its use has not improved the rates of right ventricular failure, mortality, and hospitalization [28,63,64]. The use of angiotensin-converting enzyme inhibitors (ACE-I) and angiotensin receptor blockers (ARB) 30-day post-LVAD implantation has been shown to decrease the incidence of overall GI bleeding [65,66].…”
Section: Assessment and Management -Long-term Gi Bleedingmentioning
confidence: 99%